Households' perception of arsenic-contaminated water and determinants of piped water connection in arsenic-contaminated areas in the red river delta, Vietnam (EEPSEA, 2017)
This is repost introduce about households' perception of arsenic-contaminated water and determinants of piped water connection in arsenic-contaminated areas in the red river delta, Vietnam.